6-Gingerol Attenuates Ischemia-Reperfusion-Induced Cell Apoptosis in Human AC16 Cardiomyocytes through HMGB2-JNK1/2-NF-κB Pathway. (11th February 2019) - Zhang, Weiyue; Liu, Xiaoyan; Jiang, Yiping; Wang, Nani; Li, Feng; Xin, Hailiang
Abstract : Myocardial ischemia/reperfusion (I/R) injury is a key factor in deterioration of myocardial function. The c-Jun NH2-terminal kinase (JNK) activation and the transcription factor nuclear factor-kappaB (NF- κ B) nuclear translocation have been found in I/R injury. 6-Gingerol, an important bioactive ingredient of ginger, has been reported to have cardiovascular pharmacological effects. However, the molecular mechanism through which it is beneficial is unclear. In this work, I/R induced the increase in the apoptosis and reactive oxygen species level in AC16 cardiomyocytes. 6-Gingerol administration decreased cardiomyocyte apoptosis and improved oxidative stress indexes. 6-Gingerol administration also inhibited I/R-induced HMGB2 expression upregulation and JNK activation and reduced Cleaved Poly(ADP-ribose) polymerases (PARP) and Caspase-3 expression. HMGB2 treatment mimicked the effect of I/R-induced cell damage, which was reversed by 6-gingerol administration. On the other hand, transcriptional activity of NF- κ B was reduced in 6-gingerol treated cells. Thus, overall results indicated that 6-gingerol administration protected I/R-induced cardiomyocytes apoptosis via JNK/NF- κ B pathway in the regulation of HMGB2. This work supported the efficacy of 6-gingerol on cardiovascular disease and partially revealed its mechanism, which was helpful for understanding the therapeutic effects of this natural drug.